Capecitabine after Surgical Salvage in Recurrent Squamous Cell Carcinoma of Head and Neck. (15th August 2017) - Manohar, Poorni M.; Sapir, Eli; Bellile, Emily; Swiecicki, Paul L.; Pearson, Alexander T.; Prince, Mark E.; Shuman, Andrew G.; Bradford, Carol R.; Chepeha, Douglas B.; Wolf, Gregory T.; Eisbruch, Avraham; Worden, Francis P.; et al.
Abstract : Due to the high incidence of recurrent squamous cell carcinoma of the head and neck and the toxicity profile of current salvage regimens, there is a need for tolerable and effective treatment options. We performed a retrospective matched case series to report our experience with recurrent high‐risk patients who received capecitabine (CAP) therapy in the adjuvant setting after salvage therapy. The 5‐year recurrence‐free survival rates for the CAP and control cohorts were 54% (95% CI, 0.27%‐0.75%) and 27% (95% CI, 0.09%‐0.50%), respectively. Multivariable Cox modeling showed a significant improvement in recurrence‐free survival in the CAP cohort (hazard ratio, 0.19; 95% CI, 0.04‐0.92; P =. 0392). While this was a respective analysis that could not control for all variables, these exploratory findings offer insights that may inform a prospective study to determine CAP efficacy.